Concepções e experiências de profissionais de saúde de uma Rede de Atenção Psicossocial sobre o Projeto Terapêutico Singular - Sousa, Érica Santiago (2023)
The Singular Therapeutic Project (PTS) constitutes an important assistance, management and training strategy for the equipment of the Psychosocial Care Network (RAPS) in the Unified Health System (SUS). It has been incorporated in different ways, with weaknesses in both the way of understanding and operating this resource. This qualitative-interpretative study aimed to investigate the conceptions and experiences of the construction of the PTS in the RAPS of a small municipality in the interior of São Paulo. 19 RAPS workers and managers participated, through questionnaires and semi-structured interviews, analyzed using the thematic content analysis technique. Three sets of analytical categories resulted: PTS itself; Organization of services and influencers on the use of PTS in RAPS; Articulation of RAPS and comprehensive and intersectoral care strategies. It was evident that understandings of the PTS tend to simplify its dimensions, suppressing its formative and reflective character, as well as mischaracterizing the procedural and participatory dimension of its construction. The articulation between RAPS points generally occurs through individual initiatives, without devices that facilitate the institutionalization of network care. In this sense, we strongly recommend training investment in PTS as a strategy for comprehensive care and more effective management in mental health. We recognize the PTS as a means of inducing the strengthening of municipal health policy linked to Permanent Health Education. This research arises from the researcher's involvement as a SUS worker and ends with concrete perspectives of products for local workers and managers (training workshops), and indirectly to RAPS users, due to the potential for transforming care practices.